STRATEGI LAYANAN BK DALAM MENDUKUNG PERKEMBANGAN PESERTA DIDIK TUNAGRAHITA DI SEKOLAH KHUSUS NEGERI 01 KOTA SERANG - Shinta Fatmala; Yahdinil Firda Nadirah (STKIP Subang, 2026)
The purpose of this study is to determine how effective Guidance and Counseling (BK) services are in helping students with intellectual disabilities at the Special State School (SKIN) 01 in Serang City to develop A descriptive quantitative method was used, involving interviews with mentoring teachers and literature studies The results indicate that the BK service approach is empathetic, individualized, and continuous. Concrete learning methods, visual media, daily evaluations, and habituation of polite values are provided as services Collaboration with BK teachers and parents supports the program It is proven that methods such as role-playing, humanistic approaches, sociodrama, and reinforcement of Islamic values successfully improve the academic, social, and emotional abilities of students with intellectual disabilities.